Effects of temperature and Zn2+ ion concentration on the single-stranded polyC conformation in neutral solution - Sorokin, V.A.; Usenko, E. L.; Valeev, V.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
The dependence of the polyC helicity degree on the temperature and the Zn2+ ion concentration in cacodylate buffer (pH 7, 0.015 M Na+) is studied by the methods of differential UV-spectroscopy and thermal denaturation. PolyC atoms coordinating Zn2+ ions were ascertained. Temperatures and zinc concentrations were established, at which the transition of polyC melted chains into an ordered structure being stabilized with intrachained connections N3−Zn2+−N3 was observed.